Crosstalk Between T and B Cells in the Germinal Center After Transplantation. Issue 4 (April 2017) - Kwun, Jean; Manook, Miriam; Page, Eugenia; Burghuber, Christopher; Hong, Jungjoo; Knechtle, Stuart J.
Abstract : Abstract: Crosstalk between B and T cells in transplantation is increasingly recognized as being important in the alloimmune response. T cell activation of B cells occurs by a 3-stage pathway, culminating with costimulation signals. We review the distinct T cell subtypes required for B-cell activation and discuss the formation of the germinal center (GC) after transplantation, with particular reference to the repopulation of the GC after depletional induction, and the subsequent effect of immunosuppressive manipulation of T cell-B cell interactions. In addition, ectopic GCs are seen in transplantation, but their role is not fully understood. Therapeutic options to target T cell-B cell interactions are of considerable interest, both as immunosuppressive tools, and to aid in the further understanding of these important alloimmune mechanisms. Abstract : Kwun et al provide an in-depth review on the T cell subtypes, cytokines and molecules regulating B cell activation and germinal center development, and therapeutic options to control donor-specific B cell responses and antibody production.